Indonesia’s G20 Presidency: Agenda Setting and Rulemaking towards Post-Pandemic Governance - Hidayatullah, Nur Luthfi; Afniansyah, Tengku Zalfa Zahira; Putra, Mohammad Chiesa Bagus (Center for Integrative International Studies Laboratory, Faculty of Political and Social Sciences, UIN Sunan Ampel Surabaya, 2023)
This descriptive qualitative research utilizes the concept of global governance to examine Indonesia’s contribution towards post-pandemic governance during its G20 presidency. The authors argue that Indonesia’s G20 presidency contributed towards global governance through agenda setting and rulemaking. This research has found out that in terms of agenda setting, Indonesia is capable of proposing a criteria of global health standards to anticipate future pandemics; initiate cooperation between G20 member states to digitalize the global economy for common prosperity; and promote cleaner energy sources for sustainable energy transition. In terms of rulemaking, Indonesia’s G20 presidency managed to formulate the G20 Bali Leaders’ Declaration. However, Indonesia faced challenges in implementation and monitoring, to ensure the G20 member states’ adherence towards the G20 Bali Leaders’ Declaration after Indonesia’s G20 presidency is over.